HUBUNGAN PENGGUNAAN BETADINE SALEP TERHADAP KEJADIAN FLEBITIS PADA TEMPAT PEMASANGAN INFUS INTRAVENA DI RUMAH SAKIT TENTARA TINGKAT IV 01.07.01 PEMATANGSIANTAR TAHUN 2021 - Kuat Sitepu; Anita Srigandaria Purba; Arfah May Sara; Widya . (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
Background : The incidence of ebitis is one indicator of the quality of hospital services with the standard set by The Infusion Nursing of Practice, which is 5%. The incidence of phlebitis is an indicator of minimum hospital service quality with a standard incidence of â‰¤1.5%. Purpose : Knowing the effect of using betadine ointment on the incidence of phlebitis at the intravenous infusion site at the Army Hospital TK IV. 01.07.01 Pematangsiantar. Methods : This type of research the researcher used was a quasi experiment with the equivalent control group design. The research instrument used was an observation sheet with a sample of 30 patients who had an intravenous infusion attached. Results: There was a significant effect of using betadine ointment on the incidence of phlebitis on intravenous infusion therapy. Statistical analysis using normality test, homogeneity and hypothesis testing. Conclusions and suggestions : The use of betadine ointment against the incidence of phlebitis at the intravenous infusion site has a significant relationship. Therefore the hospital management must continue to make efforts to improve services to patients. As a suggestion, room nurses should increase their knowledge through training on infection control and prevention, nosocomial infection prevention training in hospitals.